Renal Cell Carcinoma Metastatic to Thyroid Gland, Presenting Like Anaplastic Carcinoma of Thyroid - Khalid Riaz; Mutahir A. Tunio; Mushabbab AlAsiri; Asim Ali Elbagir Mohammad; Muhammad Mohsin Fareed (Case Reports in Urology)
Background. Renal cell carcinoma (RCC) has unpredictable and diverse behavior. The classic triad of hematuria, loin pain, and abdominal mass is uncommon. At time of diagnosis, 25%–30% of patients are found to have metastases. Bones, lungs, liver, and brain are the frequent sites of metastases. RCC with metastasis to the head and neck region and thyroid gland is the rarest manifestation and anaplastic carcinoma behaving metastatic thyroid mass is an extremely rare presentation of RCC. Case Presentation. A 56-year-old Saudi man with past history of right radical nephrectomy 5 years back presented with 3 months history of rapid increasing neck mass with dysphagia, presenting like anaplastic thyroid carcinoma. Tru-cut biopsy turned out to be metastatic renal cell carcinoma. Patient was treated with radiation therapy 30 Gy in 10 fractions to mass. Patient died 4 months after the discovery of anaplastic thyroid looking metastasis. Conclusion. Rapidly progressing thyroid metastases secondary to RCC are rare and found often unresectable which are not amenable to surgery. Palliative radiotherapy can be considered for such patients.